2022
DOI: 10.3389/fpsyg.2022.925162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 16 Weeks of Cheerleading on Physical Self-Esteem and Mental Health of Female College Students

Abstract: ObjectiveThis study aimed to analyze the influence of cheerleading on female college students’ physical self-esteem and mental health.Materials and MethodsIn total, 63 female college students from the University of Electronic Science and Technology of China were trained in cheerleading for 16 weeks. The scores of each sub-field of physical self-esteem and psychological symptoms were analyzed by using Physical Self-Perception Profile (PSPP) and Symptom Checklist 90 (SCL-90), respectively, at 0 and 16 weeks of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Therefore, it is necessary to recognize the negative influence of anxiety caused by insomnia, to find the comorbidities that manifest as insomnia, to assess and manage in a timely manner, to detect early, and to intervene early in order to reduce the risk of future development and promote better sleep quality and duration. In order to avoid a series of adverse effects, especially anxiety [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to recognize the negative influence of anxiety caused by insomnia, to find the comorbidities that manifest as insomnia, to assess and manage in a timely manner, to detect early, and to intervene early in order to reduce the risk of future development and promote better sleep quality and duration. In order to avoid a series of adverse effects, especially anxiety [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…If patients integrate and internalize these illness experiences and negative emotions, a sense of stigma will be formed in their psychology, which will lead to a decline in self-esteem [ 34 ], and further increase negative emotions such as inferiority complex, anxiety and depression. It indicates that self-esteem is significantly correlated with mental health and physical health [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study proves that physical exercise positively predicts the self-esteem of college students. Studies have shown that physical activity positively affects self-esteem ( Deng et al, 2022 ). Regular exercise improves the levels of self-efficacy, self-esteem, and body awareness of young adults ( Gulsum et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It indicates that self-esteem is signi cantly correlated with mental health and physical health (Deng et al, 2022).…”
Section: Mediating Mechanism Of Self-esteemmentioning
confidence: 99%